Assessment of educational potential in Arouca and Estrela UNESCO Global Geoparks (Portugal) for multi-level students and teachers - Jesús Enrique Martínez-Martín; Pilar Ester Mariñoso; Emmaline M. Rosado-González; Alexandra Paz; Artur A. Sá (International Journal of Geoheritage and Parks)
The current trend in education is to adopt a direct and efficient system that adapts to the needs of students at all levels. This approach emphasizes the importance of creating an accessible and enjoyable learning environment that integrates with the social context. The main purpose of this study is to gain a comprehensive understanding of the educational contribution of UGGps, irrespective of their level, origin, or purpose of visit, beyond the acquisssition of knowledge. The UNESCO Global Geoparks (UGGps) are recognized as educational models in the field of geosciences and sustainability due to their territorial management plan and purpose. This study examines the activities carried out in the Arouca and Estrela UGGps in Portugal, using validated questionnaires to gather feedback from students and teachers. The analysis aims to identify the strengths, challenges, and overall effectiveness of these UGGps as an alternative approach to multidisciplinary education. With a total sample of 325 students and 167 teachers, the results, from the students and teachers perspective, show a positive and valid environment for multilevel education reflected on a positive answer rate of 86% among students and 88% among teachers. As it is shown in the results, UGGps are valid territories for multilevel teaching of Earth Sciences and many other subjects. This conclusions represent a great opportunity to promote heritage protection and sustainable development education from these territories, something that, in fact, is extremely relevant in the social context in which we find ourselves.